THE CREATION AND THE ASSESSMENT OF THE BIOTECHNOLOGICAL VALUE OF THE LACTOBACILLI COMPOSITION - І. В. Страшнова; А. І. Матковська; О. В. Басюл (Mìkrobìologìâ ì Bìotehnologìâ. Мікробіологія і біотехнологія, 2016)
Aim. To determine the biotechnological potential of lactobacilli isolated from raw meat and collection strains and the compositions which were created on their bases. Methods. Lactobacilli isolated from the meat samples through passages in the skim milk sample, followed by passages on MRS -agar and broth. The collection strains were previously precultured in MRS -broth with 5% glucose. The acid production was determined from the active and titratable acidity, the activity of the coagulation of milk – on the duration of clot formation, the antagonistic activity to the collection opportunistic and pathogenic bacteria – the well-diffusion method, withingenus antagonism – the method of perpendicular grooves, the resistance to NaCl and phenol at low positive temperatures – on the growing rate in MRS -broth, the antibiotic resistance – the disk diffusion method. Results. The strains of lactic acid bacteria were isolated from the raw meat. The isolated strains are characterized by different indicators of active and titratable acidity, the coagulation rate of milk and the originality formed clot. Both isolated from meat samples, and collection strains of lactobacilli showed a variable antagonistic activity to test-strains of S. aureus, E. coli, P. vulgaris, B. cereus, S. enteritidis. Depending on the strain lactobacilli showed the resistance (it was shown in the different growth rate ), or sensitivity to 5.0% and 7.0% NaCl; 0.2% and 0.4% phenol by culturing at 5 °C and 10 °C. The investigated lactobacilli were either resistant or weakly sensitive to the antibiotics which were used. Based on strains of Lactobacillus sp. M6, L. delbrueckii ssp. bulgaricus 444 and L. plantarum 991 with more pronounced properties were created 6 variants of compositions which were determined for the same properties as the individual strains.The highest antagonistic activity, the growth rate in 7.0% NaCl and 0.4% phenol at 5 °C, the antibiotic resistance were showed by the compositions of Lactobacillus sp. M6+L. delbrueckii ssp. bulgaricus 444 in the ratio 2:1 and Lactobacillus sp. M6+L. plantarum 991 in the same ratio. Conclusions. The obtained results of the tested strains indicate the presence of lactic acid bacteria needed for the meat industry biotechnological properties, the extent and stability of which is increased in the compositions. The most promising for the industrial testing are compositions of Lactobacillus sp. M6+L. delbrueckii ssp. bulgaricus 444 and Lactobacillus sp. M6+L. plantarum 991 in the same ratio of 2:1.